Hubungan Marketing Mix Dengan Loyalitas Pasien Rawat Jalan di Rumah Sakit Tk II 14.05.01 Pelamonia Makassar - Ali Imran; Hastuti Hastuti; Rusnita Rusnita; Sriyani Windarti; Reski Dewi Pratiwi; Muslimin B; Theresa Tondok (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
The marketing mix is a key strength of hospitals, closely linked to patient behavior in utilizing services. Product mismatch with patient perceptions is a common problem in the marketing mix. Patients sometimes do not know the cost, which can be burdensome for them. Promotion does not reach the right target segment. Place refers to the location, where there are often long queues at the outpatient clinic. People rely on specific individuals or doctors for care. Process involves inefficient service delivery workflows, and physical facilities are insufficient and not fully optimized. Similarly, in Pelamonia Hospital, the marketing mix is now structured as the 10P or mega marketing mix. This theory by Dr. Samsi Jacobalis led to the decision to expand the marketing mix from 4P to 10P, which includes People, Public, Power, Pressure, and Performance. The objective of this study is to determine the relationship between the marketing mix and patient loyalty at Pelamonia Hospital TK II 14.05.01 in Makassar. The research was conducted quantitatively using a cross-sectional approach. The population consisted of 8,134 patients, with 269 samples. The sampling method used was purposive sampling. The study was conducted in April 2025 and analyzed using univariate and bivariate analysis. The results and conclusions indicate a significant relationship between the product dimension (p=0.0027), promotion (p=0.002), physical evidence (p=0.027), process (p=0.000), performance (p=0.007), public relations (p=0.026), and power (p=0.000) with patient loyalty at the outpatient department of TK II 14.05.01 Pelamonia Hospital in Makassar. There is no relationship between the dimensions of price (p=0.180), place (p=0.664), and people (p=0.713) and the loyalty of outpatients at Pelamonia Makassar General Hospital TK II 14.05.01. It is recommended that the hospital maximize its marketing mix activities to provide good service to patients and make them feel comfortable in receiving services and examinations at the hospital. Keywords: Loyalty, Marketing mix, Hospital, Outpatient